COMPARATIVE TEST OF EFFECTIVENESS OF ALCOHOL MIXTURE BASE HAND SANITIZER WITH CHLORHEXIDINE MIXTURE BASE ON ESCHERICHIA COLI AND SHIGELLA SONNEI BACTERIA - rahmi, eldiza puji; Farida Muti, Annisa; Pradana, Dhinga Luthfiyani; Valentino, Mikhael; Cahyadi, Salwa Nisrina; Andini, Putri; Ferdian, Muhamad; Widjaja, Tiyon; Razan Fachrudin, Brooklyn; Nabila, Annisa Hasna; Wandira, Salsabilla Puteri; Marliah Saputri, Sirly; Azzahra, Khayla Shifa; Kusumaningrum, Alfina Aprilia; Shabrina, Cut Laila Nur; Nurjannah, Rabbiah Putri (Journal of Research in Pharmacy and Pharmaceutical Sciences, 2023)
ABSTRACT Hand sanitizer is a hand cleanser which is easy and practical in use. Using hand sanitizer can be an alternative for washing hands if in condition without water and soap. Hand sanitizer is used to clean pathogens on hands. The ability to kill pathogens in hand sanitizers is due to the active substance content in them. In this research, the effectiveness of 2 hand sanitizers on the market was tested. The test aims to see the effect of the active substances in each preparation on the effectiveness of killing pathogens. Testing was carried out using the Kirby Bauer method and on 2 bacterial media, namely Escherichia coli and Shigella sonnei. Hand sanitizer 1 has a composition consisting of 70% ethyl alcohol and 0.5% chlorhexidine. Hand sanitizer 2 has a composition consisting of 55% ethyl alcohol and 18% isopropyl alcohol with a total of 73% alcohol. Based on observations, it was found that hand sanitizer 1 was more effective than hand sanitizer 2. The chlorhexidine content in hand sanitizer 1 increased its effectiveness in killing pathogens.